DEVELOPMENT OF INDEPENDENT CHARACTER AND RESPONSIBILITY THROUGH THE IMPLEMENTATION OF P5 AT SD AL MARDLIYAH - Ilham Faiqul Hakim Amrulloh; Nur Asiyah (Auladuna: Jurnal Pendidikan Dasar Islam, 2025)
The Strengthening of Pancasila Student Profile Project (P5) is part of Indonesia's independent curriculum, focusing on developing learner characteristics such as independence and responsibility. This study aimed to determine how P5 implementation develops independent and responsible characters in students. A qualitative case study approach was used, focusing on grade V and VI students at Al Mardliyah Elementary School. Data were collected through observation and qualitative analysis techniques. The results showed that P5 implementation successfully shaped students' independent and responsible characters through activities that internalized Pancasila values. Key activities included proper waste disposal, congregational prayers, flag ceremonies, group deliberations, and environmental maintenance. These activities effectively integrated Pancasila principles into daily school practices, promoting character development through practical application. The study demonstrates that systematic implementation of value-based activities significantly contributes to character formation. Based on these findings, P5 project implementation is recommended for developing students' independent and responsible character in elementary education.